How silver influences the structure and physical properties of chalcogenide glass (GeS2)(50)(Sb2S3)(50) - Fraenkl, Max; Frumarová, Božena; Podzemná, Veronika; Šlang, Stanislav; Beneš, Ludvík; Vlček, Milan; Wágner, Tomáš (Elsevier Science BV, 2018)
The presented study shows how the incorporation of silver changes the structure and physical properties of chalcogenide glass (GeS2)(50)(Sb2S3)(50). Nine samples with silver content (0-25 at. %) were studied to give a detailed picture. The structure and its changes were analyzed by Raman spectroscopy. The medium range order of the (GeS2)(50)(Sb2S3)(50) glass was identified. The structural motif of interconnected SbS3/2 pyramids is the doorway for the silver incorporation in the (GeS2)(50)(Sb2S3)(50) glass. The material hardness is significantly increased by up to 26% due to silver addition. The ability of silver to fill cavities in a glass is responsible for the observed hardness increase. Electronic properties and silver ion mobility were examined by impedance spectroscopy and radioactive tracer diffusion. The purpose of the presented study is to give an instructive description of how silver change the structure of the studied chalcogenide glass and give a complex feeling of how the silver changes its physical properties.
Jak ovlivňuje stříbro strukturu a fyzikální vlastnosti chalkogenidového skla (GeS2)(50)(Sb2S3)(50)
Keywords: Silver doping; Chalcogenide glasses; Hardness; Impedance spectroscopy; Radioactive tracer diffusion; dopace stříbra; chalkogenidová skla; tvrdost; impedanční spektroskopie; difúze radioaktivní značky